Heart rate variability as important approach for assessment autonomic modulation - Maycon Jr Ferreira; Angelina Zanesco (Universidade Estadual Paulista (UNESP), 2016)
Abstract Alterations in the heart rate recovery and heart rate variability have been associated with greater risk of mortality and early prognosis of cardiac diseases. Thus, strategies for assessing autonomic nervous system and its modulation to the heart are crucial for preventing cardiovascular events in healthy subjects as well as in cardiac patients. In this review, an update of studies examining heart rate variability (HRV) and its use as indicator of cardiac autonomic modulation will be discussed. It will be described the indexes and methods of analysis and its applicability and the effects of exercise training on HRV and heart rate recovery in different population.